Thomas–Fermi screening of a moving surface charge - Kulik, I.O. (Физика низких температур, 1997)
The dynamical screening effects in the skin layer of a metal are investigated. The electric charge density near the metal surface induced by a moving charged body outside the metal is screened at the Thomas–Fermi length if the velocity parallel to the surface is smaller than the Fermi velocity. Crisis of screening is found at the velocity approaching the Fermi velocity, which results in the electric field penetration inside the metal at large distances, and in the distortion of the electric field distribution outside the metal. The energy dissipation from a moving charged body as a function of the velocity has a pronounced singularity near the Fermi velocity.